Sheathing Bracing Requirements for Cold-formed Steel Wall Panels: Experimental Investigation. (June 2019) - Selvaraj, Sivaganesh; Madhavan, Mahendrakumar
Abstract: This paper presents an experimental investigation to arrive at minimum sheathing requirements to inhibit the lateral torsional buckling (LTB) of the hat-shaped cold-formed steel (CFS) member subjected to out-of-plane loading. This study also describes the need for explicit minimum sheathing requirement provisions for different geometries of CFS structural members which are currently absent in the present design specifications. The design parameters for wall panels such as slenderness of the CFS member, the thickness of the sheathing board, the spacing between the fasteners that connect the sheathing and CFS member are considered in the experimental tests. A total of 30 full-scale tests (24 sheathed panels and 6 unsheathed tests) were carried out to study the behaviour of unsheathed CFS stud, sheathed panel and to determine their corresponding ultimate moment capacities. While all the unsheathed inverted hat-shaped CFS studs failed in LTB, the CFS stud with the gypsum sheathing effect did not undergo lateral torsional buckling and the sheathing effect led to reach its corresponding yield moment which is significantly higher than the lateral torsional buckling moment of the unsheathed CFS stud. It was also observed that until the failure of CFS stud, the gypsum sheathing did not experience damage (no bearing or pull-through failure). Based on the experimental investigation, it is shown that the gypsum sheathing board of thickness ( t b ) 12.5 mm with intermediate fastener spacing ( d f ) 300 mm is sufficient to inhibit the LTB of the inverted hat shaped CFS studs. In addition, the analytical investigations were also performed to check the strength of the sheathing bracing. The analytical investigation results showed a good agreement with the experimental results in terms of sheathing failure mode and bracing requirement. Hence, the explicit minimum sheathing requirements to inhibit the LTB of the different geometry of CFS studs are suggested conservatively by considering the practicality of the wall construction.